2012
DOI: 10.1143/apex.5.042301
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Metal Impurities and Small-Angle Grain Boundaries on Recombination Properties in Multicrystalline Silicon for Solar Cells

Abstract: Recombination properties at small-angle grain boundaries (SA-GBs) in multicrystalline silicon were evaluated. After Fe contamination, the electron-beam-induced current (EBIC) contrast at most SA-GBs became stronger, especially at >1.5°. After Al gettering, EBIC contrast of most <1.5° SA-GBs became as weak as before contamination. Then, some EBIC contrast of >1.5° SA-GBs showed comparable contrast before gettering. In addition, there were SA-GBs which have different recombination properties even with the same m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…A notable outlier to this trend is seen in Figure 5d, where the grain boundary with greatest misorientation also had the lowest EBIC contrast after polishing. This replicates the work by Sameshima [35], who found that misorientation was not the sole indicator of recombination activity.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…A notable outlier to this trend is seen in Figure 5d, where the grain boundary with greatest misorientation also had the lowest EBIC contrast after polishing. This replicates the work by Sameshima [35], who found that misorientation was not the sole indicator of recombination activity.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…5 left) are assigned to low-angle GBs (misorientation angle of less than 15°) and stacking faults. It is reported that low-angle GBs are effective gettering sites for impurities due to their particular boundary dislocation structure, thus, they are strongly recombination active [24], [25]. Twin boundaries do not affect the PL signal substantially.…”
Section: Grain Boundary Characterizationmentioning
confidence: 99%
“…GB segregation would take place so as to reduce both the strain energy and the electronic GB energy (Seager, ), and effects of the segregation levels on solar cell performance have been examined for various GB structures with different tilt angles and boundary planes (Buonassisi et al ., ; Chen & Sekiguchi, ; Yu et al ., ; Sameshima et al ., ). Small‐angle tilt boundaries (SATBs), of which the tilt angle is smaller than about 10°, are composed of arrays of edge dislocations whose density is determined by the tilt angle.…”
Section: Introductionmentioning
confidence: 97%
“…In the present work, we have summarized all the APT data and constructed the comprehensive mechanism for the oxygen segregation at GBs: it is hypothesized that oxygen atoms preferentially segregate at the atomic sites under specific atomic stress so as to attain more stable bonding network by reducing the local stress. This finding would help to engineer the distribution of oxygen agglomerates at GBs in controlled fashions (Falster & Voronkov, ), as well as to control metallic contaminants by phosphorous diffusion gettering (Sameshima et al ., ; Fenning et al ., ; Seibt et al ., ) and thermal (Buonassisi et al ., ) processes, disturbed by oxygen agglomerates.…”
Section: Introductionmentioning
confidence: 98%